Meteorological data from Mycklemossen, S-mast-2 - Skogaryd Research Catchment (University of Gothenburg, 2025)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Skogaryd Research Catchment (2025). Meteorological data from Mycklemossen, S-mast-2, 2014 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/uIbFCXHC9ZHfg5xRIJzfJmHU
Keywords: Skogaryd Research Catchment; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Air temperature; Air temperature; Relative humidity; Relative humidity; Air pressure; Air pressure; Wind speed; Wind speed; Wind direction; Wind direction; Incoming shortwave radiation; Incoming shortwave radiation; Outgoing shortwave radiation; Outgoing shortwave radiation; Incoming longwave radiation; Incoming longwave radiation; Outgoing longwave radiation; Outgoing longwave radiation; Net radiation; Net radiation; Snow depth; Snow depth; Water table depth; Water table depth; Soil temperature; Soil temperature; Soil heat flux; Soil heat flux; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap